Nuclear grade and comedo necrosis of ductal carcinoma in situ as histopathological eligible criteria for the Japan Clinical Oncology Group 1505 trial: an interobserver agreement study. (8th January 2021) - Tsuda, Hitoshi; Yoshida, Masayuki; Akiyama, Futoshi; Ohi, Yasuyo; Kinowaki, Keiichi; Kumaki, Nobue; Kondo, Yuzuru; Saito, Akihisa; Sasaki, Eiichi; Nishimura, Rieko; Fujii, Satoshi; Homma, Keiichi; et al.
Abstract: Objective: The Japan Clinical Oncology Group 1505 trial is a single-arm multicentre prospective study that examined the possibility of non-surgical follow-up with endocrine therapy for patients with low-grade ductal carcinoma in situ . In that study, the eligible criteria included histopathological findings comprising low to intermediate nuclear grade and absence of comedo necrosis, and cases were entered according to the local histopathological diagnosis. Nuclear grade is largely based on the Consensus Conference criteria (1997), whereas comedo necrosis is judged according to the Rosen's criteria (2017). The purpose of this study was to standardize and examine the interobserver agreement levels of these histopathological criteria amongst the participating pathologists. Methods: We held slide conferences, where photomicrographs of haematoxylin–eosin-stained slides from 68 patients with ductal carcinoma in situ were presented using PowerPoint. The nuclear grade and comedo necrosis statuses individually judged by the pathologists were analysed using κ statistics. Results: In the first and second sessions, where 22 cases each were presented, the interobserver agreement levels of nuclear grade whether low/intermediate grade or high grade were moderate amongst 29 and 24 participating pathologists, respectively (κ = 0.595 and 0.519, respectively). In the third session where 24 cases were presented, interobserver agreement levels of comedo necrosis or non-comedo necrosis were substantial amongst 25 participating pathologists (κ = 0.753). Conclusion: Although the concordance rates in nuclear grade or comedo necrosis were not high in a few of the cases, we believe that these results could provide a rationale for employing the present criteria of nuclear grade and comedo necrosis in the clinical study of ductal carcinoma in situ . Abstract : The interobserver agreement levels of these histological criteria of nuclear grade and comedo necrosis that are employed for case entry in a clinical trial were moderate to substantial amongst pathologists.